THE ROLE OF CUSTOMARY INSTITUTIONS IN IMPLEMENTING CUSTOM LAW TO THE IMMORAL ACTS OF TILANG VILLAGE - Yosefina Elfiana; Danar Aswim; Gisela Nuwa (Institut Pendidikan Indonesia, 2022)
This study aims to examine the extent to which the Role of Customary Institutions in Applying Customary Law to Immoral Acts and to find out what are the inhibiting factors of Customary Institutions in Applying Customary Law to Immoral Acts. This research method was carried out with a qualitative approach. The data sources used are primary data sources and secondary data sources. The informants involved in the research were the Customary Institution, the Village Secretary, and the Village Consultative Body. Data collection techniques used are observation techniques, interviews and documentation studies. Data analysis techniques include data reduction, data presentation and verification. The results of the research show that the Role of Traditional Institutions as Helping to Resolve Conflicts or Problems, Places of Mediation and Participation. The inhibiting factors for customary institutions in applying customary law to immoral acts are low public awareness of the law, educational factors and association factors. This study suggests that the Tilang Village government together with the Customary Institution reaffirm customary law regarding immoral acts in new village regulations, so that they are not static but dynamic and in the administration of governance if there are differences in norms or national law and customary law, solutions and anticipation are needed fast.